EU Pre-accession Process of Turkey – Determinants and Prospects - Szymański, Adam (Wydział Nauk Politycznych i Dziennikarstwa UAM, 2015)
This article concerns the current pre-accession process of Turkey and the question of its prospects. In order to answer this question the author conducts an in-depth analysis of factors that can influence the process on three main levels: EU (i.e. general political and economic situation, EU enlargement policy, EU institutions), member states and Turkey. He wants to verify the hypothesis that although the situation in this candidate country is crucial for the future of Turkey-EU relations, the decisive factors are in the EU and member states. The pre-accession process of Turkey will be continued but its pace and course will depend to a large extent on the position of the main Union’s powers, the clear vision of the EU as well as the economic/political situation and public feelings in Europe.

Artykuł dotyczy obecnego procesu przedakcesyjnego Turcji oraz pytania o jego perspektywy. W celu odpowiedzi na to pytanie autor przeprowadza szczegółową analizę czynników, które mogą wpłynąć na proces w trzech głównych wymiarach: UE (tj. ogólna sytuacja polityczna i gospodarcza, polityka rozszerzania UE, unijne instytucje), państwa członkowskie oraz Turcja. Chce potwierdzić hipotezę, że chociaż sytuacja w kraju kandydującym jest kluczowa dla przyszłości stosunków Turcja-UE, to jednak decydujące czynniki znajdują się po stronie UE i państw członkowskich. Proces przedakcesyjny Turcji będzie kontynuowany, jednak jego tempo oraz przebieg będzie w dużym stopniu zależał od stanowiska głównych graczy w UE, klarownej wizji Unii, jak również sytuacji gospodarczej i politycznej w Europie oraz nastawienia opinii publicznej.
Proces przedakcesyjny Turcji – uwarunkowania i perspektywy akcesji do UE
Keywords: European Union; member state; Turkey; enlargement; Unia Europejska; państwo członkowskie; Turcja; rozszerzenie